The Significance of Frankincense in Grain Offerings - Grossman, Jonathan (Journal of Biblical literature, 2019)
According to Lev 2, frankincense is offered along with grain offerings, although this is mentioned in relation to the fine flour offering and not in relation to prepared grain offerings. This article proposes that the function of the addition of frankincense is to create a "sweet savor" for nonanimal offerings, which, in contrast to animal offerings, do not produce a good smell when they are burned. There is therefore no need to burn frankincense along with prepared grain offerings because baking or frying of the grain also produces a good smell that symbolizes the "sweet savor" associated with voluntary offerings.